2020
DOI: 10.1111/jocd.13779
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of interleukin‐22 in patients with cutaneous warts: A case‐control study

Abstract: Warts are viral cutaneous infections caused by human papilloma virus (HPV), presented by verrucous growth over the skin surface. 1 Its histopathological features entail keratinocyte hypercornification. 2 Around two-thirds of lesions can be spontaneously healed within 2 years without therapy. 3 The immune response is considered to play a crucial role in HPV clearance. It depends on intact cellular immunity including natural killer (NK) cell and cytotoxic T cells. It has been clarified that T-helper (Th) 1 cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The effect of IL-22 on KC susceptibility to viral infection is incompletely studied. Anecdotal evidence observed in a single clinical case study showed that more severe HPV infection (as measured by wart count) positively correlated with IL-22 levels in the serum, supporting our observation that this cytokine promotes cutaneous viral susceptibility [43]. Our findings support the hypothesis that unique cytokine signatures present in the skin, e.g., subjects with the greatest expression of IL-4, IL-13, and IL-22, would be at most risk of experiencing disseminated viral infections.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of IL-22 on KC susceptibility to viral infection is incompletely studied. Anecdotal evidence observed in a single clinical case study showed that more severe HPV infection (as measured by wart count) positively correlated with IL-22 levels in the serum, supporting our observation that this cytokine promotes cutaneous viral susceptibility [43]. Our findings support the hypothesis that unique cytokine signatures present in the skin, e.g., subjects with the greatest expression of IL-4, IL-13, and IL-22, would be at most risk of experiencing disseminated viral infections.…”
Section: Discussionsupporting
confidence: 88%
“…Warts are a contagious skin disease primarily caused by human papillomavirus (HPV) [ 123 ]. In comparison with healthy controls, patients with warts produced more IL-22 in the serum, and their IL-22 levels were positively related to the wart counts, suggesting that IL-22 is involved in the immune response against HPV [ 124 ]. Yellow fever (YF) is endemic in the tropics and is characterized by acute fever, jaundice, and proteinuria [ 125 , 126 ].…”
Section: Th22 Cells In Infectious Diseasesmentioning
confidence: 99%
“…Warts are benign verrucous lesions caused by human papillomavirus (HPV) infecting epidermal or mucosal cells. 1 There are several types of warts, including common, filiform, plane, periungual, planter, oral, and genital (condylomata acuminata) warts. Warts are usually asymptomatic, and approximately 50% of cutaneous warts disappear over 1-2 years.…”
Section: Introductionmentioning
confidence: 99%